Exploring the Effectiveness of Concept-Based Instruction Versus Deductive Methods in Teaching English Grammar - Ponna Wang; Buehler Ricard; Zhou Guang (Advances Educational Innovation, 2024)
Objective: This study investigates the impact of Concept-Based Instruction (CBI) compared to deductive methods on English grammar knowledge, student engagement and overall student teacher satisfaction in Sihanoukville, Cambodia.Methods: A quasi-experimental design was used with two groups of student teachers. In the CBI group, the experimental group was taught using CBI, while the control group used deductive methods. Grammar knowledge was assessed with pre- and post-tests, and student engagement and satisfaction were measured through observation and surveys. Statistical analyses were performed on the data to evaluate the effect of each teaching method.Results: The results showed that the CBI group significantly outperformed the control group in grammar knowledge, and they also reported significantly higher levels of engagement and satisfaction. Through CBI, students learned in an active, collaborative and meaningful way, thus improving learning outcomes.Novelty: By extending the evidence base for the effectiveness of CBI in language teaching in Cambodia, this study adds to the growing body of data supporting these claims, particularly in relation to the practice of CBI in teaching in Cambodian contexts. It also explores how a task and collaborative learning perspective can be applied to improve student outcomes in English language teaching.Theoretical and policy implications: The study confirms that CBI is effective in English language teaching and is consistent with the principles of constructivist learning theories. Based on the findings, they reflect on the implications for policy makers and educators and suggest that CBI could be integrated into language curricula to create more dynamic and effective learning environments.